Association of Life’s Essential 8 with the prevalence and mortality of chronic obstructive pulmonary disease - Shi, Yushan; Huang, Di; Liu, Yaobei; Huang, Ning (Frontiers in Medicine, 2025)
ObjectiveTo study the correlation between Life’s Essential 8 (LE8) and the occurrence of chronic obstructive pulmonary disease (COPD) among US adults, as well as the association between LE8 and all-cause and cardiovascular disease (CVD) mortality among individuals with COPD.MethodsData from National Health and Nutrition Examination Survey (2005–2018 year) were analyzed. The correlation between LE8 scores and the prevalence of COPD was evaluated using logistic regression models. Additionally, the Cox proportional hazards model was applied to investigate how LE8 scores relate to the risk of mortality from all causes and cardiovascular diseases. To ensure the robustness of the findings, sensitivity analyses and subgroup analyses were performed.ResultsIn the overall population, an inverse relationship was observed between a 10-point increase in LE8 score and the risk of COPD [OR = 0.78, 95%CI (0.75 ~ 0.82), p < 0.001]. Those diagnosed with COPD experienced a 65% increased rate of all-cause mortality and 5% higher rate of mortality due to cardiovascular diseases compared to the non-COPD group. Within the COPD patient cohort, an inverse relationship was similarly observed between a 10-point increase in the LE8 score and the risk of all-cause mortality [HR = 0.87, 95%CI (0.8 ~ 0.95), p = 0.002]. However, no significant association was found between the LE8 score and CVD mortality [HR = 0.83, 95%CI (0.68 ~ 1.02), p = 0.073]. In further exploration through subgroup analysis, no statistically significant interactions were found, suggesting consistency across different demographic or clinical subgroups.ConclusionHigher LE8 adherence is linked to lower COPD prevalence and all-cause mortality, yet no clear link to CVD mortality was found. This highlights the need for more extensive research to clarify LE8’s role in CVD outcomes.